Ciprofloxacin and statin interaction: a cautionary tale of rhabdomyolysis. (28th July 2016) - Goldie, Fraser Charles; Brogan, Amy; Boyle, James Graham
Abstract : A 62-year-old woman presented to hospital, on general practitioner (GP) advice, with a 15-day history of slowly progressing muscle weakness. Results showed newly deranged liver function and creatine kinase (CK) of >24 000. Prior medical history includes previous myocardial infarction and recurrent urinary tract infection. 4 days prior to symptom onset, the patient developed typical urinary tract infection symptoms, treated with ciprofloxacin. The patient had been taking simvastatin (40 mg nocte) for 13 years and had never previously taken ciprofloxacin. Initial management included intravenous crystalloid fluids and discontinuation of simvastatin. CK level fell, liver function slowly improved and renal function remained stable. Muscle weakness improved and the patient became independently able to perform activities of daily living. While the interactions between statins and other antibiotics are well documented, the interaction between statins and ciprofloxacin is less so. The consequences of this interaction can have potentially serious outcomes.